Gerontological nursing - Eliopoulos, Charlotte (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
"Eliopoulos provides students with the content they need, taking a holistic approach to gerontological nursing. Updated for currency, the text works to ensure students are prepared for their careers with new real world application and care competencies to help guide work place decisions. With DocuCare availability, this new edition also connects textbook resources with clinical and simulation setting via supplementary resources."--Amazon
Unit 1 Understanding the Aging Experience -- Chapter 1 The Aging Population -- Chapter 2 Theories of Aging Chapter -- 3 Diversity -- Chapter 4 Life Transitions and Story -- Chapter 5 Common Aging Changes -- Unit 2 Foundations of Gerontological Nursing -- Chapter 6 The Specialty of Gerontological Nursing -- Chapter 7 Holistic Model for Gerontological Nursing -- Chapter 8 Legal Aspects of Gerontological Nursing -- Chapter 9 Ethical Aspects of Gerontological Nursing -- Chapter 10 Continuum of Care in Gerontological Nursing -- Chapter 11 Self-Care for the Gerontological Nurse -- Unit 3 Fostering Connection and Gratification -- Chapter 12 Sexuality and Intimacy -- Chapter 13 Spirituality -- Unit 4 General Care Concerns -- Chapter 14 Nutrition and Hydration -- Chapter 15 Rest and Sleep -- Chapter 16 Comfort and Pain Management -- Chapter 17 Safety -- Chapter 18 Safe Medication Use -- Unit 5 Facilitating Physiological Balance -- Chapter 19 Respiration -- Chapter 20 Circulation -- Chapter 21 Digestion and Bowel Elimination -- Chapter 22 Urinary Elimination -- Chapter 23 Reproductive System Health -- Chapter 24 Movement -- Chapter 25 Neurologic Function -- Chapter 26 Sensation -- Chapter 27 Endocrine Function -- Chapter 28 Integumentary Function -- Chapter 29 Immune Function -- Unit 6 Multisystemic Disorders -- Chapter 30 Infections -- Chapter 31 Cancer -- Chapter 32 Mental Health Disorders -- Chapter 33 Delirium and Dementia -- Unit 7 Gerontological Care Issues -- Chapter 34 Living in Harmony with Chronic Conditions -- Chapter 35 Rehabilitative Care -- Chapter 36 Acute Care -- Chapter 37 Long-Term Care Chapter -- 38 Family Caregiving -- Chapter 39 End-of-Life Care
Includes index.
Keywords: GERIATRIC NURSING